EVALUASI PELAKSANAAN PROGRAM KESEHATAN JIWA DI PUSKESMAS BANDONGAN KABUPATEN MAGELANG - Rahayu, Aprillia Nur; Indrawati, Fitni (Jurnal Kesehatan Masyarakat (Undip), 2021)
The performance achievements of Mental Health UKM at the Bandongan Health Center that must be carried out regularly are the coverage of health services for people with severe mental disorders, KKJ meetings every three months as well as KKJ assistance in the three fostered villages. However, in 2020 there was a Covid-19 pandemic which resulted in delays in the implementation of activities as in previous years. The purpose of the study was to evaluate the implementation of the Mental Health program at the Bandongan Health Center.This type of research is qualitative. The technique of taking informants is purposive sampling. The number of samples in the study were 10 informants. The instrument used is an interview guide, observation and documentation. Data is analyzed and presented in narrative form.The results showed that implementing human resources were sufficient but there was no certified mental health training for implementing officers. Mental examination activities are carried out in the general poly room, facilities for health promotion and education about mental health are available at the Puskesmas. The source of funds comes from the BOK. Planning for program implementation is not yet available during the pandemic. Treatment services for ODGJ patients continue to run as usual so that treatment services for ODGJ patients are achieved 100%, but for the implementation of counseling, socialization and cadre meetings, cadre training, and visits to ODGJ patients do not run optimallySuggestions for this research are to plan the implementation of the program in a pandemic.